Shifting Imperatives: An Integrative View of Resource Scarcity and Agency Reasons for Franchising - Castrogiovanni, Gary J.; Combs, James G.; Justis, Robert T. (Entrepreneurship Theory and Practice, 2006)
Alternative explanations of franchising offer contrasting predictions as to how the proportion of franchised outlets changes as franchisors age. We propose that two dominant views—resource–scarcity and agency theory—can be integrated by delineating when each is most relevant. Data from 102 franchisors over a 21–year period suggest that resource–scarcity considerations take precedence when franchisors are young, but that agency considerations prevail as franchisors age. Thus, the proportion franchised exhibits a cubic pattern as franchisors age—increasing rapidly at first, decreasing, and then increasing again. Future researchers and practitioners alike can benefit from understanding how the relative influences of resource and agency considerations shift over time.